THE INFLUENCE OF EDUCATION FUNDING MANAGEMENT AND LEARNING FACILITIES ON MADRASAH QUALITY - Virgin Sabrina El-Islamy; Samsul Susilawati; Munirul Abidin (Managere: Indonesian Journal of Educational Management, 2023)
This study aims to determine how the management of education funding affects the quality of education and the impact of financing, management, and learning environment on the quality of education. This research was conducted on school principals and teachers at MAN 4 Kediri to better understand the quality of schools. The research methodology used is a quantitative approach to uncover the relationship between education financing management, education quality, and the influence of the learning environment on the overall quality of MAN 4 Kediri Data collection methods include the use of Likert scale-based questionnaires, which are given to all school staff, to measure opinions and attitudes relevant to research variables Data analysis involves various quantitative techniques. Descriptive analysis is important in providing a comprehensive picture of employee leadership, performance, and productivity through an in-depth evaluation of respondents' scores. From the results of this study, it is concluded that education financing management has a low impact on the quality of schools in MAN 4 Kediri, while learning facilities contribute significantly to school quality. The practical implications of this research can be used as a guide to improve education financing management strategies and learning facilities in MAN 4 Kediri to improve the quality of education. This study makes a significant contribution in understanding the relationship between education financing management, learning facilities, and school quality in MAN 4 Kediri.